Payments for environmental services in Costa Rica: conservation and production decisions within the San Juan - La Selva Biological Corridor - Morse, Wayde C. (2007)
Tesis (Doctorado) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho, 2014